Density of acetylcholine esterase (AchE) and tyrosine hydroxylase (TH) containing fibers in the amygdala of roman high- and low-avoidance rats. (6th October 2016) - Yilmazer-Hanke, Deniz; Eliava, Marina; Hanke, Joachim; Schwegler, Herbert; Asan, Esther
Highlights: Roman High Avoidance rats better in attention and two-way active avoidance task. Good active avoidance correlates with high cholinergic input to lateral amygdala. Roman Low Avoidance rats show enhanced stress reactivity and no escape response. Enhanced stress behavior correlates with high dopaminergic input to central amygdala. Dopamine may upregulate corticotropin-releasing hormone (CRH) in central amygdala. Abstract: The cholinergic and dopaminergic innervation of the amygdala plays an important role in attention, emotional arousal, aversive forms of associative learning, conditioned responses, and stress responsivity. Roman High- (RHA) and Low-Avoidance (RLA) rats are an ideal model to study the potential impact of this innervation on behavioral responses, because they were selected bidirectionally for differences in their two-way active avoidance performance. RHA rats are known to quickly acquire two-way active avoidance and show indications of enhanced impulsive behavior, novelty seeking, and vulnerability to substance abuse, whereas RLA rats exhibit a passive coping style with high levels of immobility and enhanced stress responsivity. In the present study, the density of acetylcholine esterase (AchE)-positive cholinergic fibers and tyrosine hydroxylase immunoreactive (TH-ir) fibers were analyzed in various amygdala nuclei. In comparison to RLA rats, RHA rats displayed a significantly higher density of AchE-positive fibers in the lateral nucleus (La), the major sensory input area of the amygdala. In contrast, RLA rats showed a higher density of TH-ir fibers in the lateral division of the central nucleus (CeL), which modulates amygdala output and is known to contain more corticotropin-releasing hormone (CRH) positive neurons in RLA than in RHA rats. The findings suggest that a higher density of AchE-positive fibers in the La of RHA rats may facilitate attentional mechanisms and aversive forms of associative learning in RHA rats, whereas the increased density of TH-ir fibers in the CeL of RLA rats may be involved in the regulation of enhanced CRH expression and stress responsivity.